ANALYSIS OF INFORMATION SYSTEM IMPLEMENTATION IN BINUS UNIVERSITY USING DELONE AND MCLEAN INFORMATION SYSTEM SUCCESS MODEL AND COBIT FRAMEWORK - Kerta, Johan Muliadi; Suryawan, Angellia Debora (CommIT (Communication and Information Technology) Journal, 2013)
The success of implementation of information system in an organization will supportthe organization in the process of achieving goals. Successful information system will support theorganization's day-to-day operations, so that problem can be resolved more quickly and easily. Theinformation system which has been developed and implemented is also necessary to measure thematurity level. Therefore, it can determine whether the implementation of information systemsmade in accordance with the goals of the organization. Measuring the success of informationsystems used the DeLone and McLean IS success model. To measure the maturity level ofinformation systems used COBIT (Control Objectives for Information and related Technology)frameworks that provides best practices for IT governance and control. The results of this analysiswill assist and support the IT team in order to develop and build information systems that better fitthe needs and goals of the organization.